A Narrative Inquiry into Indonesian Pre-service Teachers' Cross-Cultural Teaching Experiences in Malaysia - Amanda Jasmine; Dewi Kurniawati; Nunun Indrasari (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study aims to gain an in-depth understanding of how Indonesian English Education students describe their teaching experiences during the 2024 International Service Learning Program in Malaysia. Employing a qualitative narrative inquiry design, data were collected through in-depth interviews and reflective narratives, then analyzed using Braun and Clarke's thematic analysis to identify recurring patterns within the participants' stories. The findings reveal three central themes: (1) cultural adjustment, reflected in students' efforts to navigate different classroom norms and communication styles; (2) pedagogical shift, demonstrated through their Adaptation of teaching strategies to meet Malaysian learners' expectations; and (3) professional identity formation, emerging through ongoing reflection on their roles as novice teachers in a cross-cultural context. These results contribute to the theoretical understanding of intercultural teacher education by highlighting the value of narrative Inquiry in capturing identity development within transnational teaching spaces. Practically, this study underscores the importance of structured intercultural preparation for pre-service teachers. At the same time, at the policy level, it emphasizes the need to expand international exposure programs to strengthen global teaching competencies.